(untitled) (Baghdad Science Journal, 2004)
74 fanners were randomily selected from the Lc:ital. of 406 fanners using the Modern Irrigation System up to November , 2000 , for the purpose of wide adoptation of such system. Rcsults indicated according to the data which has been obtained and statistically analysed by the statistical package for the Social Sciences (SPSS) program showed that the majority of the farmers adopted this new system of irrigation due to the increase in the yield up to 5" .